PELATIHAN DAN PENDAMPINGAN ANYAMAN PURUN DESA SUNGAI KALI KABUPATEN BATOLA, KALIMANTAN SELATAN - Ellisa Vikalista; Sandra Bhakti Mafriana; Markus Haposan Pakpahan; Hari Angga Dewaji; Falehah Nabila; Birhanadin Azura; Muhammad Bintang Norumansyah; Ali Zainal Abidin; Dita Nursyifa; Hesti Dwi Ameliasari; Putri Maulida; Nema Aisy Athaya (Wadah Inovasi Indonesia, 2022)
The Village of Sungai Kali is located in the riverbank of Barito which is part of swamp and wet land areas. Within the area, plant species of purun tikus or Eleocharis Dulcis is common to find. Most villagers, especially wives, have skill in knitting the purun tikus into crafting products. Nevertheless, their income is plummeting, thus they could not sustain their daily needs. This condition is due to the fact that they sell their product to the ‘middle man’. Moreover, lack of innovation is also one of the reasons the craft is not well developed. Therefore, the activity to empower the villagers is important to introduce the crafting product of Sungai Kali. The activity was conducted as part of student’s society empowerment program (KKN) with the partnership of the Division of the Small Business Entity (UMKM), District of Barambai, Barito Kuala Regency. The project was broadcasted by several local mass media, including TVRI of South Kalimantan also online media ANTARAKalsel and Kompasiana. This project aims to elevate Sungai Kali Village’s products, especially its purun crafting products, and eventually the villagers can increase their income.